RETRACTED : The Influence of Work Stress, Work Ethic and Supervision on Employee Performance at PT. Bank Central Asia, Main Branch Office Bidakara Tower - Latifah; Elwisam; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research aims to analyze work stress, work ethic and supervision of employees at PT. Bank Central Asia, Tbk, especially the Bidakara Tower Main Branch Office, with a total of 100 research samples taken from permanent employees and interns. Research results using Multiple Linear Regression Analysis show that work supervision is more dominant in influencing employee performance than work stress and work ethic. Work stress has a positive and significant effect on employee performance. Bank BCA strives to be better at managing work stress to meet employee needs and produce good performance. Work ethic also has a positive but not too big effect on employee performance. BCA Bank pays attention to a high work ethic because it is rooted in strong cooperation and strong commitment from employees. Work ethic is very important to motivate employees to improve their performance. Supervision influences employee performance more dominantly than work stress and work ethic. Good supervision will reduce the rate of work errors. Work supervision also influences employee work motivation to provide and improve their own good performance.